2019
DOI: 10.1128/mbio.02258-19
|View full text |Cite
|
Sign up to set email alerts
|

New Mitochondrial Targets in Fungal Pathogens

Abstract: In eukaryotic cells, mitochondria are responsible for the synthesis of ATP using power generated by the electron transport chain (ETC). While much of what is known about mitochondria has been gained from a study of a small number of model species, including the yeast Saccharomyces cerevisiae, the general mechanisms of mitochondrial respiration have been recognized as being highly conserved across eukaryotes. Now, Sun et al. (N. Sun, R. S. Parrish, R. A. Calderone, and W. A. Fonzi, mBio 10:e00300-19, 2019, http… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The growth of these fungi was inhibited at a phosundoxin concentration of 4 mg/L. However, C. glabrata and its cryptic species had lower susceptibility to phosundoxin than other Candida species, with MICs from 8 to 16 mg/L, implying that the mitochondrial structure or regulation of C. glabrata and its cryptic species may differ from other Candida species [37]. In addition, we found that the MICs of the yeast phase were higher than that of hyphal phase when Talaromyces marneffei was exposed to phosundoxin, indicating that phosundoxin was more effective in inhibiting the hyphal phase of dimorphic fungi.…”
Section: Discussionmentioning
confidence: 97%
“…The growth of these fungi was inhibited at a phosundoxin concentration of 4 mg/L. However, C. glabrata and its cryptic species had lower susceptibility to phosundoxin than other Candida species, with MICs from 8 to 16 mg/L, implying that the mitochondrial structure or regulation of C. glabrata and its cryptic species may differ from other Candida species [37]. In addition, we found that the MICs of the yeast phase were higher than that of hyphal phase when Talaromyces marneffei was exposed to phosundoxin, indicating that phosundoxin was more effective in inhibiting the hyphal phase of dimorphic fungi.…”
Section: Discussionmentioning
confidence: 97%
“…As an adaptation to changes in the host microenvironment and in response to host immune cell attack, the way in which C.albicans reprograms its metabolism by altering its central carbon metabolism to take advantage of alternative carbon sources is important for the maintenance of its virulence (Han et al, 2011). And the in-depth study of the respiratory chain, the main site of carbon metabolism, has not only identified respiration itself as a key condition for virulence, but also identified specific genes in the CTG branch involving the respiratory chain, offering the possibility of developing new therapeutic targets against Candida species infection ( Murante and Hogan, 2019;Sun et al, 2019). The successful development of complex III inhibitors and the mature application of complex III as a drug target in the field of pesticides have provided us with the prerequisite ideas to explore the function of the auxiliary subunits in C.albicans complex III.…”
Section: Discussionmentioning
confidence: 99%
“…For every kind of fungi, mitochondria are the hubs of respiration and metabolic activity, such as oxidative phosphorylation and the citric acid cycle, which are also involved in phospholipid metabolism [81]. Mitochondria impact multiple aspects of fungal pathogenesis, such as fungal growth, antifungal susceptibility, and the yeast-to-hypha transition [82]. Mitochondrial dysfunction decreases the activity of respiratory chain enzymes and the mitochondrial membrane potential, initially leading to damaged intracellular Ca 2+ homeostasis and blocked β-oxidation of fatty acids.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%